Improving Child Outcomes through Nursing Care: A Review - Dr. Bhagyashree Jogdeo (Indian Journal of Nursing Sciences, 2025)
This review explores the pivotal role of pediatric nursing in improving child health outcomes globally. Despite advancements, under-five mortality and child development disparities persist, underscoring the need for robust healthcare interventions. Pediatric nurses serve in diverse roles—from caregivers and educators to care coordinators—across settings such as hospitals, communities, and schools. The review examines key nursing interventions in preventive, promotive, curative, rehabilitative, and palliative care, demonstrating their impact on morbidity, mortality, and quality of life. Evidence-based practices, including clinical guidelines and comprehensive care models, have shown measurable success in improving child outcomes. However, challenges such as limited training, understaffing, and cultural barriers hinder optimal care delivery. The review calls for expanded specialized education, supportive policies, and standardized pediatric nursing indicators to strengthen nursing capacity and ensure equitable, high-quality pediatric care worldwide.